2014
DOI: 10.1016/j.scitotenv.2013.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Electro-chemical arsenic remediation: Field trials in West Bengal

Abstract: Millions of people in rural South Asia are exposed to high levels of arsenic through groundwater used for drinking. Many deployed arsenic remediation technologies quickly fail because they are not maintained, repaired, accepted, or affordable. It is therefore imperative that arsenic remediation technologies be evaluated for their ability to perform within a sustainable and scalable business model that addresses these challenges. We present field trial results of a 600 L Electro-Chemical Arsenic Remediation (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 15 publications
1
91
0
Order By: Relevance
“…These investigations have reported that arsenic adsorption onto HFO particles is fairly independent of pH up to a pH of 8. Limited available field data suggest that groundwaters in the Southern Asia area have pH levels in the near-neutral pH range 6,14 and, as seen herein, would provide a suitable aqueous environment for the application of EC technology. These groundwaters also appear to have an ionic composition (and electrical conductivity) that would also support EC-based arsenic removal systems.…”
Section: Practical Operating Considerationsmentioning
confidence: 79%
See 2 more Smart Citations
“…These investigations have reported that arsenic adsorption onto HFO particles is fairly independent of pH up to a pH of 8. Limited available field data suggest that groundwaters in the Southern Asia area have pH levels in the near-neutral pH range 6,14 and, as seen herein, would provide a suitable aqueous environment for the application of EC technology. These groundwaters also appear to have an ionic composition (and electrical conductivity) that would also support EC-based arsenic removal systems.…”
Section: Practical Operating Considerationsmentioning
confidence: 79%
“…A few HFO particles apparently were able to pass through the granular media filter bed. Alum has been used to help improve HFO particle removal in a larger scale EC system arsenic removal systems 14 . The sub-10 µg/L arsenic levels achieved after membrane filtration offer hope that an enhanced granular media filter or another size-appropriate solids separation technology can be used to meet global standards.…”
Section: Filtration Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology is particularly applicable in decentralized and rural areas because of its low infrastructure requirements, ease of use and potential for scalability [1,2]. While EC systems are often accompanied by supplementary treatment steps, including settling tanks and filters [3], the technology centers on applying an electric current to Fe(0) electrodes in contact with an electrolyte solution to promote the oxidative release of soluble Fe(II) ions [4,5]. The Fe(II) ions migrate from the Fe(0) anode surface to the bulk solution, where contaminant removal occurs by several possible pathways.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we investigated the interdependent effects of i, E A and solution composition by combining time dependent measurements of E A and total Fe released from the Fe(0) anode as a function of i and solution chemistry. To encompass the range of current densities likely applied in Fe(0) EC field treatment [3], the i of EC experiments was adjusted over two orders of magnitude (0.25-50 mA/cm 2 ). The impact on the Faradaic efficiency of a variety of dissolved species common in natural waters was studied by systematically varying the ionic composition and pH of the solution, building in complexity from single and binary anion systems to synthetic groundwater matrices.…”
Section: Introductionmentioning
confidence: 99%